Batmanacarus robini, n. gen., n. sp. (Trombidiformes: Trombiculidae) collected parasitizing a ghost-faced bat (Chiroptera: Mormoopidae) from a cave in Trinidad and Tobago - Bassini-Silva, Ricardo; Huang-Bastos, M.; Welbourn, C.; Ochoa, R.; Barros-Battesti, D. M. [UNESP]; Jacinavicius, F. C. (Springer Nature, 2021)
Trinidad and Tobago, a neotropical country, has 38 reported chigger species. Of these species, 18 were parasitizing bats. Here, we describe a new genus and species parasitizing a ghost-faced bat in this country.
Keywords: Caribbean; chigger; Chiroptera; ectoparasite; new species